Retrospective of International Serological Studies on the Formation and Dynamics of the Humoral Immune Response to SARS-CoV-2: from 2020 to 2021 - E. A. Novikova; A. G. Petrova; E. V. Moskaleva; A. S. Vanyarkinа; L. V. Rychkova (Acta Biomedica Scientifica, 2021)
Last year the COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has started. The new coronavirus is highly contagious and causes severe complications. The mechanisms of humoral immunity and kinetics of SARS-CoV-2 specific antibodies in a population are not well understood. Therefore, we aimed to summarize and analyze numerous global and Russian serological studies for understanding dynamics of the SARSCoV-2 humoral immune response and getting an accurate picture of the seroprevalence to SARS-CoV-2 in the world population. The PubMed and e-library databases were searched from February 2020 to March 2021 using terms “SARSCoV-2”, “antibodies”, “humoral immunity”. At the beginning of the pandemic first studies were cross-sectional by design and were responsible for determination of the seropositivity and for understanding the fundamental humoral immunity parameters of SARS-CoV-2. Since then, longitudinal seroepidemiological studies have been studying antibody kinetics. Seroconversion time for IgM, IgG antibodies varies, but most researchers report the seroconversion of IgM from the 1st to 14th days after the onset of clinical manifestations, and the seroconversion for IgG is around the 14th day with a concentration peak by the 21st day. Regarding seroprevalence we may say about low herd immunity at the COVID-19 pandemic. Thus, global seroprevalence is about 10 %, and more than 20 % for regions with high incidence and among healthcare workers. Seroprevalence studies have to be continued for more accurate monitoring of long-term humoral immunity to SARS-CoV-2, because the majority of the world’s population is still susceptible to SARS-CoV-2 infection.